2017
DOI: 10.1111/1365-2435.12986
|View full text |Cite
|
Sign up to set email alerts
|

Axial xylem architecture ofLarix deciduaexposed to CO2enrichment and soil warming at the tree line

Abstract: Trees continuously adjust their axial xylem structure to meet changing needs imposed by ontogenetic and environmental changes. These axial structure–function responses need to be coordinated among competing biophysical constraints to avoid failure of the xylem system. Here, we investigated if ontogeny or experimental manipulation of CO2 and soil temperature influence these structure–function responses. We performed detailed xylem cell anatomical quantification along the axis of 40‐year‐old Larix decidua trees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 95 publications
6
32
0
Order By: Relevance
“…Hence, findings of this study suggest that upward bending of basal branches, i.e., a weak apical control in the sapling stage, might be an adaptation to extreme environmental conditions prevailing in the alpine treeline ecotone in cool temperate and boreal mountains, especially during winter. Our interpretation is corroborated by strong apical control found in co-occurring European larch (L. decidua [33]), which, due to its deciduous behavior, is less prone to winter drought and snow mold.…”
Section: Protective Function Of Cluster Formation and Weak Apical Consupporting
confidence: 78%
“…Hence, findings of this study suggest that upward bending of basal branches, i.e., a weak apical control in the sapling stage, might be an adaptation to extreme environmental conditions prevailing in the alpine treeline ecotone in cool temperate and boreal mountains, especially during winter. Our interpretation is corroborated by strong apical control found in co-occurring European larch (L. decidua [33]), which, due to its deciduous behavior, is less prone to winter drought and snow mold.…”
Section: Protective Function Of Cluster Formation and Weak Apical Consupporting
confidence: 78%
“…The theoretical tree-ring hydraulic conductivity (Kh r ) was assessed as the sum of Kh c of the average radial file (Figure 1). The ratio between Kh r and RWA provided the hydraulic carbon use efficiency (HCUE; Prendin et al, 2018).…”
Section: Anatomical Measurementsmentioning
confidence: 99%
“…Summing the cell wall area (Fonti et al, 2013) of all tracheids provides an estimate of wood material in the ring (tree-ring biomass) (Björklund et al, 2019). Finally, the 'hydraulic carbon use efficiency' expresses the (yearly) theoretical tree-ring hydraulic conductivity for a given carbon investment (Prendin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, measurements performed on trees representing different levels of intrinsic growth rates in several conifers in Alpine, Temperate, and Boreal Europe indicated that the effect of summer drought in fast-growing trees does not occur in slow-growing ones [20]. In contrast, there are some characteristics of the wood structure, such as those related to hydraulic efficiency (via the tracheid lumen diameter), that are much more constrained over age and size changes, since they play a fundamental role in assimilation and growth [29].…”
Section: Introductionmentioning
confidence: 99%